Conductor and Cobbler: Leadership Lessons From Large-Scale Research Partnership Facilitation - Michelle Lam (Journal of Participatory Research Methods)
“I was a nurse, and now I’m an academic. Why would they think I know how to manage a website!?” (Colleague, personal communication). Many scholars make the transition from managing their own doctoral research project to larger-scale research involving funders, industry partners, community-based partners, or others. Although often well-prepared for research and theorizing, the leadership work of facilitation, project management, budget management, and other logistical and human aspects can be daunting and unfamiliar. This autoethnographic study examines my own experiences of making this transition, using personal notes and journal entries as data for analysis. By analyzing them through a concept of belonging (Pfaff-Czarnecka, 2011), I consider the lessons learned through a large-scale research project: a community-based project involving the creation of a connected network of rural research hubs, and how these lessons impacted my identity as a scholar and director of a research centre. I also share the process of how autoethnography can be enacted in such a role. The findings have been categorized into two metaphors: Conducting an orchestra without any music, and fitting shoes for diverse feet. These lessons offer ways of understanding the struggles and successes of learning to lead large-scale research projects while honouring the diversity of lived experiences and particularities of context, recognizing the need for all to belong within these complexities.